Deteksi Wajah untuk Presensi Menggunakan Facial Landmark - Zulkhairi Zulkhairi; Rodhiyah Mardhiyyah; RR Hajar Puji Sejati; Adam Sekti Aji (INTEK : Jurnal Informatika dan Teknologi Informasi, 2022)
The Covid-19 virus is easily spread by direct contact with other people or not. One of the media that can transmit the covid virus in the office area is a fingerprint machine because the tool is used together. Presence data is one of the data that can be used to see employee performance. To reduce the risk of spreading the COVID-19 virus, attendance can be done by performing face detection. The face detection system uses facial landmarks as markers of facial areas called facial landmark points. When the system successfully detects a face, the user can then confirm the system so that the system will record attendance time data. The result of testing on this system is that the system can detect faces when the face is not wearing a mask.